Literasi Keuangan dan Tingkat Pendidikan Terhadap Perencanaan Keuangan UMKM Pangan Jalan Payakumbuh Jakarta Selatan - Naser, Haspul; Kusuma Devi, Nurwulan; Herviana Rahmayati , Suci (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Background: MSMEs in the food sector show an important role in backup the Indonesian economy. However, financial planning challenges are often an obstacleto the sustainability of MSME businesses. Low financial literacy and formaleducation can hinder financial planning, resulting in suboptimal management andpotentially threatening business continuity. Research objectives: The presentresearch examines the impact of financial literacy and education level on thefinancial planning of MSMEs in the food sector in South Jakarta. Novelty: Thisstudy provides novelty by focusing on the combination of these two variables in thespecific context of food sector MSMEs, which has rarely been explored in previousresearch. Research methodology: Quantitative approach with survey technique.The questionnaires distribute to 100 MSMEs in South Jakarta. Findings: The studyreveals that financial literacy positively impacts MSMEs' financial planningpractices, while education level also has a positive but not significant impact.Conclusion: Financial literacy positively impacts MSMEs' financial planning, withimproved education and financial literacy contributing to better cash managementand investment planning, highlighting the importance of financial literacyprograms.